Elucidation of the Educational Discourse within the Admonitions of Luqman the Wise: توضيح البيان التربوي في وصايا لقمان الحكيم - Uthman, Yusuf Olawale Owaonire (Universitas Muhammadiyah Surakarta, 2024)
This study explores and analyzes the educational discourse embedded within the admonitions of Luqman the Wise, a historical figure renowned for his wisdom and profound contemplations. The research delves deeply into the examination of values and ethics manifested in these admonitions, exploring how they can serve as a significant source of inspiration and guidance for personal development and societal advancement. The study addresses the cultural and religious context in which Luqman's admonitions originated, shedding light on how the educational discourse is reflected in the teachings of Islam. Methodologically, the study employs a meticulous approach to Quranic texts related to Luqman's admonitions, drawing support from relevant prophetic traditions (hadith). The research undertakes an in-depth analysis of the Quranic context that distinguishes Luqman's admonitions, with a specific focus on their impact in delineating values and educational guidelines associated with Islam. Additionally, the research draws upon specific Quranic references to support a profound analysis of the educational values within Luqman's admonitions. For instance, the Quran 31:13-19, alludes to the wisdom of Luqman the Wise and his sagacious guidance to his son, underscoring the significance of the Islamic understanding of these admonitions. Therefore, these admonitions worth to be recommended for an individual in our current society.